The Effects Of Superior-Subordinate Relationship And Justice Perception On Organizational Commitment And Job Involvement - Perumal, Subramaniam (2005)
This research paper examines the impact of interpersonal working relationship and justice on job satisfaction, turnover intention and ultimately employees' commitment to the organization and their level of involment in their resent job in Malaysian scenario. The Leader-Member Exchange (LMX) theory is used to explain these relationships.